2019
DOI: 10.1111/all.13773
|View full text |Cite
|
Sign up to set email alerts
|

The change in the prevalence of wheeze, eczema and rhino‐conjunctivitis among Japanese children: Findings from 3 nationwide cross‐sectional surveys between 2005 and 2015

Abstract: In conclusion, we have found reversing trends in the prevalence of wheeze and eczema but not in rhino-conjunctivitis among Japanese children. One in three children still had one or more allergic disease, underlining the importance of further research into the risk factors and possible prevention strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 9 publications
2
30
0
Order By: Relevance
“…A 2015 study reported that the prevalence of wheeze in Japanese children at age 6-8 years was 10.2% [1]. Our study group previously identified five phenotypes in the trajectory of wheeze in Japanese children [2].…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…A 2015 study reported that the prevalence of wheeze in Japanese children at age 6-8 years was 10.2% [1]. Our study group previously identified five phenotypes in the trajectory of wheeze in Japanese children [2].…”
Section: Introductionmentioning
confidence: 58%
“…The same study reported that the prevalence of rhinoconjunctivitis in children at age 6-8 years was 18.7% and that the prevalence of nasal conjunctivitis had been increasing for ten years [1]. Allergic rhinitis usually decreases QOL and is associated with sleep disturbance and reduced daily activity [6,7].…”
Section: Introductionmentioning
confidence: 97%
“…Asthma exacerbation cases are responsible for a large number of emergency department visits, hospitalization, and healthcare expenditures each year in the most developed countries [1, 2]. In Japan, asthma affects 8–13% of children [3, 4]. Among them, approximately 15% were uncontrolled, and <5% experienced severe wheeze in the past year [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In Japan, asthma affects 8% to 13% of children. 3,4 Among them, approximately 15% were uncontrolled and less than 5% experienced severe wheeze in the past year. 4,5 According to most guidelines for the treatment of patients hospitalized for asthma exacerbation, 6,7 the standard treatments consist of oxygen administration, inhaled short-acting b 2 -agonists, and systemic corticosteroids.…”
mentioning
confidence: 99%
“…3,4 Among them, approximately 15% were uncontrolled and less than 5% experienced severe wheeze in the past year. 4,5 According to most guidelines for the treatment of patients hospitalized for asthma exacerbation, 6,7 the standard treatments consist of oxygen administration, inhaled short-acting b 2 -agonists, and systemic corticosteroids. Some current guidelines 6,8 recommended against routine antibiotic prescription for asthma exacerbations in the absence of concurrent bacterial infections because respiratory viral infections are the major cause of asthma exacerbations.…”
mentioning
confidence: 99%